ANALISIS KANDUNGAN GIZI, TOTAL POLIFENOL DAN SERAT PANGAN SNACK BAR BIJI HANJELI DENGAN PENAMBAHAN BUBUK KOKOA - Muhammad Rizki Purnama (2021)
The prevalence of cardiovascular disease due to hyperlipidemia globally increases every year. This can be handled by consuming a diet high in polyphenols and dietary fiber. The purpose of this study was to determine the effect of adding cocoa powder on nutritional content, total polyphenols, dietary fiber content and organoleptic properties of job's tears snack bars. This research used a completely randomized design (CRD) with three levels of treatment for the addition of cocoa powder; F1 (5%), F2 (7.5%) and F3 (10%). Analysis of organoleptic test data and chemical properties using the Kruskal-Wallis test and ANOVA test. The results of the study on the organoleptic test indicated that there was a significant effect of adding cocoa powder on the level of preference for the panelists on the parameters of color, taste and texture (p <0.05). The results of the analysis of total polyphenols of job's tears snack bar with the addition of cocoa powder had a significant effect (p <0.05) on the increase in the polyphenol value of the snack bar. The best treatment was found in the addition of cocoa powder F2 (7.5%) which was acceptable to the panelists and had a chemical composition per serving (50 grams); energy (235 kcal), water (5.37%), ash (0.77%), protein (4.69%), fat (11.94%), carbohydrates (27.2%), dietary fiber (7.25%) and total polyphenols (62.5mg / 50g GAE).